2021
DOI: 10.1080/23311975.2021.1960120
|View full text |Cite
|
Sign up to set email alerts
|

The role of green investment and corporate social responsibility investment on sustainable performance

Abstract: Studies on green investment and corporate social responsibility (CSR) investment has been conducted by some researchers in the current and future trends of sustainable development. Many of them have focused on the relationship between CSR and financial performance, but only a few have examined how green investment, CSR investment, and sustainability are related to each other. Sustainable performance is based on three aspects: people-planet-profit, or also what is known as the triple bottom line concept. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 83 publications
6
67
0
2
Order By: Relevance
“…These findings are consistent with those of earlier studies [5,7,13], which found that GF significantly enhances SP. Likewise, green investment has a significant beneficial influence on an organization's SP [14]. Furthermore, the literature has confirmed that GI significantly enhances the environmental performance of an organization [8,25].…”
Section: Findings and Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These findings are consistent with those of earlier studies [5,7,13], which found that GF significantly enhances SP. Likewise, green investment has a significant beneficial influence on an organization's SP [14]. Furthermore, the literature has confirmed that GI significantly enhances the environmental performance of an organization [8,25].…”
Section: Findings and Discussionmentioning
confidence: 82%
“…Moreover, Xu et al [23] have shown that GF improves corporate green performance significantly. Green investment has a considerable positive influence on the firm's financial and SP, according to Indriastuti and Chariri [14]. Although the relationship between GF and firm environmental sustainability is extensively documented in the literature, there has been less emphasis on the interaction of FA, GF, GI, and SP in a single study.…”
Section: Green Finance and Sustainability Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Legitimacy theory emphasizes the significance of social consent in promoting a company's long-term viability [31]. It is widely believed that the phenomenon of corporations making voluntary social and environmental disclosures is explained by legitimacy the-ory [32].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…GI is seen as a driver for realising CSR initiatives aiming to improve corporate performance in a sustainable way. However, there are not many few studies on how GI, CSR efforts and SBP are linked together (Indriastuti & Chariri, 2021). In addition, from the resource‐based view (RBV) theory, GI and CSR are seen as corporate resources and capabilities to promote the implementation of green innovation (GIN) leading to SBP (Barney, 1991).…”
Section: Introductionmentioning
confidence: 99%